2022
DOI: 10.3390/ijms232415602
|View full text |Cite
|
Sign up to set email alerts
|

SP600125 Enhances Temperature-Controlled Repeated Thermal Stimulation-Induced Neurite Outgrowth in PC12-P1F1 Cells

Abstract: This study evaluated the mechanism of temperature-controlled repeated thermal stimulation (TRTS)-mediated neuronal differentiation. We assessed the effect of SP600125, a c-Jun N-terminal kinase (JNK) inhibitor, on neuronal differentiation of rat PC12-P1F1 cells, which can differentiate into neuron-like cells by exposure to TRTS or neurotrophic factors, including bone morphogenetic protein (BMP) 4. We evaluated neuritogenesis by incubating the cells under conditions of TRTS and/or SP600125. Cotreatment with SP6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The two subclones were derived from PC12 parental cells based on their TRTS sensitivity during TRTS-mediated neuronal differentiation. Based on the new evidence acquired from the experiments using these novel subclones, the authors suggested that the BMP pathway may be required for TRTS-induced neurite outgrowth [4,7].…”
Section: Thermal Stimulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The two subclones were derived from PC12 parental cells based on their TRTS sensitivity during TRTS-mediated neuronal differentiation. Based on the new evidence acquired from the experiments using these novel subclones, the authors suggested that the BMP pathway may be required for TRTS-induced neurite outgrowth [4,7].…”
Section: Thermal Stimulationmentioning
confidence: 99%
“…It can form synapses with primary cultured neurons isolated from the rat cerebral cortex [3]. PC12 cells differentiate into neuron-like cells when exposed to neurotrophic factors, including nerve growth factor (NGF) [2,4]. NGF binds to its membrane receptor, tropomyosin-related kinase A (TrkA), which is expressed in these cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations